Rehabilitación postquirúrgica en la lesión de tendón rotuliano - Arichabala Montenegro, Miguel Andres (Machala: Universidad Técnica de Machala, 2023)
The purpose of rehabilitation is to optimize the individual's physical activities, social participation and quality of life, whether acute or chronic, by means of different interventions that allow the recovery of the total or partial functionality of the injured joint. Objective: To understand the importance of an adequate rehabilitation of the patellar tendon injury through the review of scientific articles in order to achieve a correct reintroduction of the operated patient to his daily life. Materials and methods: the present study is a descriptive, retrospective study where bibliographic reviews of health articles were performed within the last 5 years such as: UpToDate, Sensors, Pubmed, Journal of arthroscopic and related surgery, journal of sports science & medicine, which are updated sources for relevant medical information. Conclusion: A proper rehabilitation protocol for a patellar tendon injury may include strengthening exercises, stretching, physical therapy, manual therapy, and other treatment modalities. It is important to follow the rehabilitation protocol consistently and under the supervision of a healthcare professional.
La rehabilitación tiene como finalidad la optimización de las actividades físicas del individuo, su participación social, y su calidad de vida, ya sean estas agudas o crónicas, mediante las distintas intervenciones permite la recuperación de la funcionalidad total o parcial de la articulación lesionada. Objetivo: Comprender la importancia de una adecuada rehabilitación de la lesión del tendón rotuliano mediante la revisión de artículos científicos para lograr una correcta reintroducción del paciente operado a su vida cotidiana. Materiales y métodos: el presente estudio es descriptivo, retrospectivo donde se realizaron revisiones bibliográficas de artículos de la salud dentro de los últimos 5 años como por ejemplo: UpToDate, Sensors, Pubmed, Journal of arthroscopic and related surgery, journal of sports science & medicine, que son fuentes actualizadas para información médica relevante. Conclusión: Un adecuado protocolo de rehabilitación para una lesión del tendón rotuliano puede incluir ejercicios de fortalecimiento, estiramientos, terapia física, terapia manual y otras modalidades de tratamiento. Es importante seguir el protocolo de rehabilitación de manera constante y bajo la supervisión de un profesional de la salud.
Keywords: REHABILITACIÓN; TENDÓN ROTULIANO; TERAPIA FÍSICA; RODILLA